(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
When women were used in classical antiquity to solve problems unsolvable by traditional means, these priestesses and witches represented nothing more than a common belief in the knowledge of society at that time, although it is already known that some could represent evil forces. Time passed and, with the advent, above all, of religious magical thinking, fueled by these folklores from the past, women involved in rituals representing some kind of power, in this case related to the spiritual, were literally demonized and, in this way, removed from the spaces social and, when “stubborn”, burned. In order to understand how this imaginary of extermination/hate to women has not ceased, this work draws a parallel between them and the construction of the narrative that the maleficae have not disappeared: they currently hide like a wolf in sheep’s clothing behind soft speeches “communists” in the faces of a Manuela Dávila, a Maria do Rosário, a Dilma Rousseff or Marielle Franco, according to bolsonarism.